A pilot study of grocery store sales: do low prices=high nutritional quality?. Issue 1 (2014) - Barbara Exum; Sharon H. Thompson; Leslie Thompson
<x xml:space="preserve"> Abstract </x> Purpose – Low fruit and vegetable intake is associated with heart disease, some cancers, and other major causes of death. Product pricing influences food purchases and economic declines have affected food budgets; therefore, this study examined the nutritional quality of advertised meal deals and buy‐one‐get‐one free (BOGO) offers at three major grocery store chains over ten weeks. The paper aims to discuss these issues. Design/methodology/approach – USDA's SuperTracker and Diet Analysis Plus were used for nutritional analyses of advertised offers over a ten‐week time period in Fall 2011. Findings – Meal deal – ten‐week averages per person: prices ranged from $1.25 to $5.00. Evaluation of MyPlate categories revealed the following percentage breakdown: empty calories – 57 percent, grains – 21 percent, protein – 12 percent, dairy – 8 percent, vegetables – 2 percent, and fruit – 0 percent. BOGO – ten‐week averages: when examining MyPlate categories, nutritional quality was similar to meal deals in that few products were from the vegetable (12 percent) fruit (4 percent), and dairy (3 percent) groups. Originality/value – Research is sparse regarding nutritional quality of advertised sales at grocery stories.